The Helpless Protecting the Vulnerable? Defending Coerced Mothers Charged with Failure to Protect - Midson, Brenda (Victoria University of Wellington Law Review, 2014)
In a number of jurisdictions failure to protect a child from violence renders a person liable if a duty is owed to the child. This duty presumes the defendant has the capacity to act positively to protect the victim, which has implications for defendants who are also subjected to violence or coercion. In the understandable haste to prosecute and prevent child abuse, there is a risk of neglecting the realities of other vulnerable people. Consequently the criminal justice system ought to reject a binary approach to victims and offenders, recognising that defendants may also be victims and that mothers, due to the coercive control exerted by intimate partners, may also be vulnerable. In New Zealand there are no statutory or common law defences that operate to exculpate a mother charged with failing to protect her child from the violence of another. This article argues for the creation of an affirmative defence that takes into account the totality of a coerced mother’s circumstances in considering whether she has, in fact, failed her child.